Modern Belarusian strategy of society development - Shavel, Sergey A. (Journal of the Belarusian State University. Sociology, 2022)
The paper presents a realised analysis of the formation and content of the modern strategy of socio-economic, cultural and political development of the Belarusian society. The tasks of the social policy of the Republic of Belarus are defined. The reasons why the liberal path and liberal tendencies are not supported in Belarus are exposed in the article. The liberal approach assumes some incorrectness, which lies in the fact that the strategic choice of each ethnic group can be made not by deciphering the historical question: Quo vadis? («Who we are, where we are from and where we are going?»), and by a certain joining to the models of some other peoples. And this incorrectness is emphasised. The main characteristics of the modern Belarusian strategy are revealed. They are the social orientation of the state, protection and guarantees of life support, the priority of a person, social groups and categories of the population. They also include the most significant foreign policy dispositions – a course to maintain integration with Russia within the framework of the Union State of Belarus and Russia, friendly relations with all countries and peoples who are ready and agree to equal relations in the field of trade and cultural exchange.